Theory of mind in adolescents with Attention-Deficit Hyperactivity Disorder: A cross-sectional study - Razjouyan, Katayoon; Hosseinzadeh, Mariam; Zahed, Ghazal; Khademi, Mojgan; Davari, Rozita; Arabgol, Fariba (Iranian Journal of Child Neurology, 2023)
Objective Attention-Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder which may be associated with impaired Theory of Mind (ToM) and social cognition. ToM is a domain in social cognition which refers to one’s ability to attribute beliefs, intents, perspectives, and understandings to oneself or others and to understand other’s mental state. Materials & Methods The present study enrolled 52 ADHD of adolescents and 41 healthy age-matched controls in this study. This study applied The Reading the Mind in The Eyes Task (RMET) and Theory of Mind Assessment Scale (Th.o.m.a.s.) for all participants. The results of these tasks were compared between the two study groups. Results e no significant differences between these two study groups in terms of ToM abilities using mean scores in Th.o.m.a.s inventory and the Reading the Mind in the Eyes test. Also, we did not find any association between the mean score in ToM (in both study groups) and our study parameters of gender, mean age, birth rank, family structure, and income. Conclusion This study did not support the hypothesis that adolescents with ADHD perform worse on ToM tasks.